Systematic Literature Review : The Role Of Digital Technology In The Implementation Of Independent Curriculum In Elementary Schools - Wandira, Rifa Yuli; Firmansah, Deri; Negara, Hasan Sastra (JURNAL ARMADA PENDIDIKAN, 2025)
Gaps in the implementation of the Independent Curriculum in elementary schools are still visible, especially in the uneven and optimal use of digital technology in various regions. This research aims to regularly examine the role of digital technology in supporting the implementation of the Independent Curriculum at the elementary school level. The research uses the Systematic Literature Review (SLR) approach by analyzing relevant articles through the Google Scholar, Garuda, DOAJ, and ResearchGate databases. From the initial search process of 200 articles, based on inclusion and exclusion criteria, 15 scientific articles published in 2020-2025 were screened that were suitable for analysis. The data was analyzed using thematic coding techniques. The results of the analysis show that digital technology plays an important role in improving the quality of learning that is more interactive, adaptive, and contextual in accordance with the Independent Curriculum. However, challenges such as limited infrastructure and teacher competence are significant obstacles.